Neural Functions of Matrix Metalloproteinases: Plasticity, Neurogenesis, and Disease - Hiromi Fujioka; Yusuke Dairyo; Kei-ichiro Yasunaga; Kazuo Emoto (Biochemistry Research International)
The brain changes in response to experience and altered environment. To do that, the nervous system often remodels the structures of neuronal circuits. This structural plasticity of the neuronal circuits appears to be controlled not only by intrinsic factors, but also by extrinsic mechanisms including modification of the extracellular matrix. Recent studies employing a range of animal models implicate that matrix metalloproteinases regulate multiple aspects of the neuronal development and remodeling in the brain. This paper aims to summarize recent advances of our knowledge on the neuronal functions of matrix metalloproteinases and discuss how they might relate in neuronal disease.